Optimizing Autonomic Function Analysis via Heart Rate Variability Associated With Motor Activity of the Human Colon - Ali, M. Khawar; Liu, Lijun; Chen, Ji-Hong; Huizinga, Jan D. (Frontiers in Physiology, 2021)
The parameters of heart rate variability (HRV) can non-invasively assess some autonomic activities, and HRV is influenced by many bodily actions. Although parasympathetic activity is the primary driver of colonic propulsive activity, and sympathetic activity a major inhibitor of colonic motility, they are rarely measured and almost play no role in diagnosis of colon motor dysfunction or in standard treatments. Here we set out to optimize HRV analysis of autonomic nervous system changes related to human colon motility. The electrocardiogram and impedance were recorded in synchrony with colonic motor patterns by high-resolution manometry. Respiratory sinus arrhythmia (RSA), root mean square of successive differences of beat-to-beat intervals (RMSSD), the Baevsky Index or Sympathetic Index (SI), and the ratios of SI/RSA and SI/RMSSD were shown to indicate a marked increase in parasympathetic and withdrawal of sympathetic activity during the high-amplitude propagating pressure waves (HAPWs). Strong associations were seen with HAPWs evoked by a meal and rectal bisacodyl indicating a marked increase in parasympathetic and withdrawal of sympathetic activity during the gastrocolic reflex and the defecation reflex. When HAPWs occurred in quick succession, parasympathetic activation (RSA and RMSSD) occurred in a rhythmic fashion. Hence, during propulsive motor patterns, an overall shift in autonomic activity toward increased parasympathetic control was shown to be reflected in HRV. HRV assessment may therefore be valuable in the assessment of autonomic dysfunction related to colonic dysmotility.